The Politics of Responsive Cookbooks: Counter Gastronomy Collectibles in Laura Esquivel’s Like Water for Chocolate - Majda R. ATIEH; Batoul DEEB (Cultural Intertexts)
This essay examines the politics of counter cookbooks whose role shifts from receptacles to responses that mobilize revolutionary culinary spaces in the war narrative of Laura Esquivel’s Like Water for Chocolate (1989). In particular, the essay redirects the main theories and critiques that have been established and espoused in culinary studies. In this reading of Like Water for Chocolate, a cross-cultural intervention in the existing scholarship on domestic spatiality and female identity is addressed. Esquivel’s narrative features provisioning collectibles that encode the mobility of the kitchen as a repository of women’s counter-discourses that not only reverse but also chaotically recreate the structured conceptions in the master war narratives. The kitchen in Esquivel’s narrative compiles cryptic scrapbooks of recipes whose technologies of knowledge are either decoded or re-inscribed from one generation to another. Arguably, women’s transgenerational gastronomic writings function as intersemiotic artefacts that activate performative subject positions in gendered households and varied social contexts that reflect the dominant power dynamics. So, Like Water for Chocolate decentralizes the impact of external wars, as it curates recipes that are ekphrazeined and recreated in foodways that empower individuals, galvanize new alliances, and decolonize female relations from the national/international ideologies of warscapes, cultural signifiers, and collective memory. The essay incorporates Homi Bhabha’s theory on the relation between the codification of history and the art of collecting to examine the discursive relations between food and power. Ultimately, this study revisits the complex dynamics of foodways as narrative functions, especially in relation to social inequalities and justice as portrayed through literature and cultural narratives.